Pengaruh Penerapan Model Pembelajaran Non Direktif Terhadap Keaktifan Belajar Peserta Didik Dalam Mata Pelajaran Pendidikan Agama Islam - Salamudin, Ceceng; Nurzakiyah, Nurzakiyah (MASAGI : Jurnal Pendidikan Agama Islam, 2023)
Student engagement during the teaching and learning process is a crucial indicator of their desire or motivation to learn. Students are considered active if they exhibit behaviors such as frequently asking questions to the teacher or peers, willingly completing assignments given by the teacher, being able to answer questions, and often being assigned learning tasks. Active participation in the learning process fosters high interaction between teachers and students, as well as among the students themselves. However, in practice, student engagement has not been fully optimized. Therefore, the non-directive teaching model is one of the options to create a refreshing and conducive learning environment.   This study aims to describe the effect of implementing the non-directive teaching model on student engagement in Islamic Religious Education (PAI) for Grade IX students at SMP Persada Cilawu. The research employed a descriptive associative method, involving direct fieldwork to observe and record the ongoing phenomena. The results from this study indicate that both student engagement and the non-directive teaching model received favorable evaluations. The findings show that the implementation of the non-directive teaching model accounts for 7.2% of the variance in student engagement, as reflected in the model summary table with a value range between 0.00 and 0.1999, indicating a very low effect. Despite this categorization as "very low," the impact of the non-directive model cannot be dismissed, as it remains an external factor that can influence student engagement in learning. The remaining 92.8% of the influence is attributed to other factors not examined in this study.  Keywords: Teaching Model, Non-Directive, Student Engagement, Islamic Religious Education